PERAN BAHASA ARAB TERHADAP PENINGKATAN KARAKTER SPIRITUAL DAN SOSIAL MAHASISWA - Nuraini, Nuraini; Ummah, Khuntum Khaira; Mustofa, Syaiful (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Good Arabic language skills can improve a person's spiritual and social character. This character includes ethics, morals and values related to moral strength with positive connotations, both the relationship between humans and God and the relationship between humans and humans. This research aims to determine the role of Arabic in improving the character of students of the Master of Arabic Language Education at Maulana Malik Ibrahim State Islamic University (UIN) Malang in 2023. This research uses a qualitative approach with descriptive methods. Data collection techniques through observation, interviews and documents. The results of this research show the role of Arabic in improving the spiritual and social character of students through three factors, namely dalil aqli, good deeds of worship, and good communication. Aqli's arguments include Arabic for sharpening thought patterns and increasing authority, Arabic for character education, and Arabic as the best language for understanding Islam. Arabic language towards increasing acts of worship including prayer, understanding the Koran, and religious insight. Arabic for good communication includes self-confidence, public speaking, and Arabic language work. These factors show that improving a person's spiritual and social character can be achieved with good Arabic language skills.